Managing technological discontinuities : the case of the Finnish paper industry - Laurila, Juha (Management of technology and innovation., 1998)
This volume describes how conflicting managerial actors become mobilized to co-operate in situations of discontinuous technological change. These ideas are explored through an in-depth study of the Finnish paper industry.